Three-dimensional virtual reality in surgical planning for breast cancer with reconstruction - De la Cruz-Ku, Gabriel (2023)
Breast surgery is performed to achieve local control in patients with breast cancer. Visualization of the anatomy with a virtual reality software platform reconstructed from magnetic resonance imaging data improves surgical planning with regards to volume and localization of the tumor, lymph nodes, blood vessels, and surrounding tissue to perform oncoplastic tissue rearrangement. We report the use and advantages of virtual reality added to the magnetic resonance imaging assessment in a 36-year-old woman with breast cancer who underwent nipple sparing mastectomy with tissue expander reconstruction.